Global migration, public order, and collective bargaining operating on borders (International Journal of Scientific Research and Management (IJSRM), 2016)
the article is a brief investigation over global migration policies, and gives a reflection over the main international and European employment sources, considering the urgency of the 2015 increasing flows and disputes at the frontiers. It gives a particular attention to collective bargaining as major tool to address labour of migrants within the legal system; a focus is set on the Italian scene for development of industrial relations, willing to have erga-omnes effects (including migrants) but suggested to take a tripartite approach (workers-state-employers) while dealing with such socially pressing matters.